Smallpox - past or not past? - Kuljić-Kapulica Nada (Srpski Arhiv za Celokupno Lekarstvo, 2004)
Smallpox is a potentially deadly illness caused by the variola virus, an orthopoxvirus. Severe illness followed by blister-like body rash is the sign of smallpox. Smallpox symptoms develop about 12 days after exposure. V. variole can spread very readily by aerosol, which may lead to explosive epidemics. For centuries, smallpox has been a worldwide cause of death, killing about 30% of the infected people. In 1972, the epidemic of smallpox in ex-Yugoslavia was the largest postwar smallpox epidemic in Europe. The total number of the affected was 175, out of whom 35 with fatal outcome, accounting for 20% of mortality. However, after a decade-long vaccination effort, the last natural case of smallpox occurred in 1977 The only way to prevent smallpox epidemic is by vaccination and patients' isolation. The possibility of future bioterrorism attacks, which may cause a new outbreak of smallpox and return variola, is very serious. World population is not immune, because of lack of vaccination. In 1980, the World Health Organization (WHO) declared the disease fully eradicated.